2019
DOI: 10.5114/fn.2019.91194
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FGD5-AS1 acts as a competing endogenous RNA for miRNA-223 to lessen oxygen-glucose deprivation and simulated reperfusion (OGD/R)-induced neurons injury

Abstract: The purpose of this study was to evaluate whether FGD5-AS1 participates in oxygen-glucose deprivation and simulated reperfusion (OGD/R)-induced neurons injury and the detailed mechanism. An OGD/R model was established using the primary cortical neuron isolated from the brains of Sprague-Dawley rats. qRT-PCR and western blot were performed to detect the RNA and protein expression levels, respectively. Cell counting kit 8 (CCK8) and flow cytometry assays were used to evaluate the proliferation and apoptosis of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…As FGD5‐AS1 has been reported to target miR‐223 in neurons, 18 we analyzed whether FGD5‐AS1 targeted miR‐223 in HCC cells. The binding site for miR‐223 in FGD5‐AS1 was shown in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As FGD5‐AS1 has been reported to target miR‐223 in neurons, 18 we analyzed whether FGD5‐AS1 targeted miR‐223 in HCC cells. The binding site for miR‐223 in FGD5‐AS1 was shown in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidences have shown vital roles of the lncRNA‐miRNA‐mRNA competing endogenous RNA (ceRNA) interaction network in human carcinomas 17 . The observations that FGD5‐AS1 directly targets microRNA‐223 (miR‐223) in neurons 18 and miR‐223 is a key regulator in HCC 19 imply that FGD5‐AS1 might regulate HCC progression via targeting miR‐223. Epithelial cell transforming sequence 2 (ECT2) and FAT atypical cadherin 1 (FAT1) are identified as novel targets of miR‐223 recently 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Jing et al also found that overexpression of LncRNA mu-1-opioid peptide receptor (Oprm1) results in the alleviation of apoptosis from cerebral I/R injury through the Oprm1/miR-155/GATA binding protein 3 (GATA3) axis ( Jing et al, 2019 ). Furthermore, the LncRNA AK038897/miR-26a-5p/death-associated protein kinase 1 (DAPK1), FGD5 antisense RNA 1 (FGD5-AS1)/miRNA-223/insulin-like growth factor (IGF)-1 receptor (IGF1R), tumor-associated LncRNA expressed on chromosome 2 (TALNEC2)/miR-650/apoptotic peptidase activating factor 1 (APAF1), FOXD3-AS1/miR-765/BCL2L13, and RNA imprinted and accumulated in nucleus (Rian)/miR-144-3p/GATA3 axes have been found to attenuate apoptosis after cerebral I/R injury ( Zhang XQ. et al, 2019 ; Wei et al, 2019 ; Lu et al, 2020 ; Yao et al, 2020 ; Chen M. et al, 2021 ; Cao et al, 2021 ).…”
Section: Regulatory Roles Of Lncrnas In Neuronsmentioning
confidence: 99%
“…FGD5-AS1 has been discovered to attenuate hypoxia-induced oxidative stress and apoptosis in human cardiomyocytes [ 29 ]. FGD5-AS1 has also exhibited an effect of extenuating oxygen–glucose deprivation and simulated reperfusion damage by increasing neuron proliferation but reducing neuron apoptosis [ 30 ]. In this study, FGD5-AS1 displayed an effect on the proliferation and apoptosis of human primary ventricular cardiomyocytes (AC16) and aortic vascular smooth muscle cells (HA-VSMC).…”
Section: Discussionmentioning
confidence: 99%